The international judicial cooperation in the Peruvian private international law system - Arriola Espino, Marcela (2007)
The Private International Law is related to different legal disciplines; for that reason, one of their important subjects within the frame of the International Procedural Law is the International Judicial Cooperation, which is called international judicial attendance. The practice of procedural acts outside the place of the process with foreign element is common, and that is possible thanks to the will of the States making the territoriality and sovereignty principle of the process not an impediment for the performance of fundamental diligences that allows to explain the controversy. This work is a brief vision about the Peruvian Private International Law System.